Efeito tripanocida da L-amino ácido oxidase isolada do veneno da Bothrops marajoensis - Pereira, Ticiana Praciano (2015)
Trypanosoma cruzi, the etiologic agent of Chagas disease, remains a p ublic health problem in the Americas. In the present study, we evaluated th e effects of L-amino acid oxidase from Bothrops marajoensis venom (BmLAAO) on the all evolutive forms of T. cruzi . Epimastigote forms of T. cruzi , were cultived in LIT medium, at 28ºC in BmLAAO pr esence for 48 and 72h. Trypomastigote were obtained from the supernat ants of infected LLC-MK 2 cells, resuspended in MEM with 2% FBS and treated for 24 h . BmLAAO showed significant activity against the epimastigote (IC 50 48h = 6.31μ g/mL; IC 50 72h = 5,85μ g μ g/mL.) and trypomastigote (LC 50 24h= 0.17μ g/mL) forms and decrease the amastigote s urvival within LLC-MK 2 . Analysis of the possible involvement of hydrogen peroxide was performed by catalase addition in medium, an enzyme that acts as H 2 O 2 scavenger. The cell death showed that the cytotoxic effect of BmLAAO is reduced but not completely abolished by the catalase presence. Confocal microscopy analysis of epimastig otes treated with BmLAAO showed staining with propidium iodide (PI), indicative of loss of membrane integrity, and loss of mitochondrial membrane potential, as observed by st aining of treated cells with Rhodamine 123 (Rho123). Besides, the flow cytometry with anne xin V and propidium iodide suggest decrease of membrane permeability. Ultrastructural analysis showed drastic morphological changes on the parasite mitochondrion with ruptured kDNA network. Increase of endoplasmic reticulum profiles, enhanced electrondensity of mit ochondrion and endoplasmic reticulum membranes, loss of the parasite inner organization, swelling of cell body with the appearance of dismantling organelles, formation of myelin-like structures indicative of autophagic activity, were also observed in treated parasites. In conclusion, the BmLAAO showed cytotoxic effects on T. cruzi and this action is only partially dependent on H 2 O 2 production by the BmLAAO. In addition, BmLAAO induced morphologic al and physiological alterations compatible with loss of viability and cell death